Re-Austenitisation of Thin Ferrite Films in C–Mn Steels during Thermal Rebound at Continuously Cast Slab Corner Surfaces - Dannis Rorisang Nkarapa Maubane; Roelf Johannes Mostert; Kevin Mark Banks (Metals, 2022)
The influence of primary cooling and rebound temperature at C–Mn slab corner surfaces during continuous casting on ferrite film transformation and AlN precipitation was investigated. Laboratory simulations included primary cooling to minimum temperature, Tmin, rebounding to various maximum temperatures, Tmax, followed by secondary cooling. The negative effect of a low Tmin on hot ductility could not be readily reversed, even at relatively high temperatures. Quantitative metallography was employed to study the evolution of the microstructure during rebounding and secondary cooling. Following primary cooling to temperatures just above the Ar3, thin films of allotriomorphic ferrite formed on the austenite grain boundaries. These films did not completely transform to austenite during the rebound at 3 °C/s up to temperatures as high as 1130 °C and persisted during slow secondary cooling up to the simulated straightening operation. Whilst dilatometry did not indicate the presence of ferrite after high rebound temperatures, metallography provided clear evidence of its existence, albeit in very small quantities. Coincident with the ferrite at these high temperatures was the predicted (TC-PRISMA) grain boundary precipitation of AlN in bcc iron during the rebound from a Tmin of 730 °C. Importantly no thin ferrite films were observed, and AlN precipitation was not predicted to occur when Tmin was restricted to 830 °C. Cooling below this temperature promotes austenite grain boundary ferrite films and AlN precipitation, which both increase the risk of corner cracking in C–Mn steels.